(untitled) (Conferencea, 2023)
This article presents the results of studying the chemical structure of coal ash. This reveals their mineralogical nature and makes it possible to identify various elements and compounds that can determine the properties of coals as potential adsorbents. Analysis of the chemical composition of ash from various coal samples showed a significant diversity in the content of key elements such as oxides of silicon, aluminium, iron and calcium. Differences in the content of SiO2 and Al2O3 between the samples are especially noticeable. Such data emphasize the need to take into account the chemical and mineralogical composition of coal when used as a starting material for adsorbents. This will optimize the characteristics of the resulting materials and increase their efficiency.